Law Enforcement Against Environmental Pollution by Vehicle Exhaust Emissions - Rahayu Subekti; Davin Gerald Parsaoran Silalahi; Dhiwa Arya Purbadi; Rismoyo Kurnia Sangkara (Kosmik Hukum, 2023)
Enforcement of environmental laws relating to emissions from motor vehicle exhaust It is clear from the laws and regulations that the Ministry of Transportation is authorized to act as the implementing agency for periodic motor vehicle inspections and emission testing. The use of motorized vehicles contributes to air pollution which hinders the management and protection of the environment. There are many types of environmental pollution, but in particular air pollution has far-reaching detrimental effects and has a significant impact on environmental quality. By using normative legal research methods and literature studies, namely research that looks at document studies, there are several regulatory matters, including Article 206 of Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Presidential Regulation (Perpres) No. 55 of 2019 concerning the Acceleration of the Battery Electric Vehicle Program for Road Transportation. One of the causes of environmental pollution, especially in the air, is the use of vehicles that use oil (fuel). Electric vehicles are currently the solution to developing environmentally friendly technologies. The government's efforts are carried out by completing emission tests and developing electric vehicles that affect both the environment and vehicle health.Keywords: Law Enforcement, Environment, Emissions, Electric Vehicles